2007
DOI: 10.1002/j.2055-2335.2007.tb00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Time Required to Provide Components of Clinical Pharmacy Services

Abstract: Aim:To determine the time spent by pharmacists on components of clinical pharmacy services using chosen recording tools. Method: A 4-week study was conducted at an acute general hospital in early 2006. Pharmacists completed Pharmaceutical Clinical Pathway (PCP) forms and recorded the time needed for its completion. Other activities not associated with completing PCP forms (e.g. medication chart review, clinical review, adverse drug reaction monitoring, therapeutic drug monitoring, provision of drug information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The recording tools were used as previously, with one modification to the PCP form-the pharmacists recorded the time to complete all details on page 1 of the form in a designated section. 12 This included the time to confirm allergy status, medication history, usual medication administration arrangements and the current location of patients' own medicines. Data recorded on page 2 of the PCP form was not used as we previously found that this information was not recorded consistently.…”
Section: Methodsmentioning
confidence: 99%
“…The recording tools were used as previously, with one modification to the PCP form-the pharmacists recorded the time to complete all details on page 1 of the form in a designated section. 12 This included the time to confirm allergy status, medication history, usual medication administration arrangements and the current location of patients' own medicines. Data recorded on page 2 of the PCP form was not used as we previously found that this information was not recorded consistently.…”
Section: Methodsmentioning
confidence: 99%
“…In the Riskman database, pharmacists used designated fields to record the dates and details of each intervention and, when required, the times involved. We earlier described the development and use of these recording tools in detail [12,13] . Subsequent references to clinical pharmacy activity by ward‐based pharmacists in this paper refer to activities measured by these tools only.…”
Section: Methodsmentioning
confidence: 99%
“…We earlier described the development and use of these recording tools in detail. [12,13] Subsequent references to clinical pharmacy activity by ward-based pharmacists in this paper refer to activities measured by these tools only. It does not refer to other activities that these pharmacists may perform that these tools do not measure, such as formal education sessions provided to other healthcare workers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations